Phytoplankton and Its Role in Accumulation of Microelements in Bottom Deposits of Azov Sea - Irina V. Dotsenko; Anna V. Mikhailenko (The Scientific World Journal)
The importance of phytoplankton is high in transformation of substances in aquatic ecosystems and in formation of suspension’s material structure. Its main functions are consumption of the dissolved biogenic components and chemical elements and their conversion to a firm phase. The article is devoted to the bioaccumulation of microelements by phytoplankton in the ecosystem of the Azov Sea. The fact that the algal biomass during the periods of blooming in the sea reaches 1,400 g/l makes this study especially urgent. The authors define the rates of biogeochemical cycle and the intensity of chemical elements’ consumption and also investigate the role of phytoplankton in the formation chemical peculiarities of bottom deposits and its involvement in sedimentogenesis in the Azov Sea. The cause of the reduced trace element content in bottom deposits relatively to suspended material is established. It is noted that the amount of some elements annually consumed by algae of the Azov Sea is up to 75% from their maximum delivery by terrigenous material.